2017
DOI: 10.1021/acs.nanolett.6b03817
|View full text |Cite
|
Sign up to set email alerts
|

Critical Behavior in Doping-Driven Metal–Insulator Transition on Single-Crystalline Organic Mott-FET

Abstract: We present the carrier transport properties in the vicinity of a doping-driven Mott transition observed at a field-effect transistor (FET) channel using a single crystal of the typical two-dimensional organic Mott insulator κ-(BEDT-TTF)CuN(CN)Cl (κ-Cl). The FET shows a continuous metal-insulator transition (MIT) as electrostatic doping proceeds. The phase transition appears to involve two-step crossovers, one in Hall measurement and the other in conductivity measurement. The crossover in conductivity occurs ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 85 publications
(208 reference statements)
0
25
0
Order By: Relevance
“…For Mott-FET fabricated with κ-type single crystal κ-(BEDT-TTF) 2 Cu-[N(CN) 2 ]Cl, mobility over 200 cm 2 V ¹1 s ¹1 was achieved, while metallic conduction was observed only at low temperature because of "the contribution from the undoped bulk channel". 5,6 In this case, the Mott gap is even smaller than the previous cases, and thus Mott insulator crystal with hundreds of nanometers thickness could not offer a high resistance like a normal organic band insulator with large HOMO-LUMO gap. Indeed, the transport carriers are accumulated only in the first few layers in FET operation, 7 while most of the layers without carrier accumulation still remain in Mott insulating state.…”
Section: Introductionmentioning
confidence: 81%
“…For Mott-FET fabricated with κ-type single crystal κ-(BEDT-TTF) 2 Cu-[N(CN) 2 ]Cl, mobility over 200 cm 2 V ¹1 s ¹1 was achieved, while metallic conduction was observed only at low temperature because of "the contribution from the undoped bulk channel". 5,6 In this case, the Mott gap is even smaller than the previous cases, and thus Mott insulator crystal with hundreds of nanometers thickness could not offer a high resistance like a normal organic band insulator with large HOMO-LUMO gap. Indeed, the transport carriers are accumulated only in the first few layers in FET operation, 7 while most of the layers without carrier accumulation still remain in Mott insulating state.…”
Section: Introductionmentioning
confidence: 81%
“…Slight modification of parameters may alter the stability of the two. Now in κ-Cl, both electron and hole doping are realized using the EDLT 46,47 . The filling-control MI transition and the emergence of SC have been confirmed with significant electron-hole doping asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, SC transition could be driven by the small carrier modulation d M ≈ 6.3 × 10 12 cm −2 corresponding to ≈0.035 electron or hole per BEDT‐TTF dimer. However, the field‐induced resistance change in device 1 is not so large as those in previous FETs based on κ‐type salts . It is probably because the upper layers of the κ‐NCS channel far from interface between channel and gate insulator have non‐negligible conductivity.…”
mentioning
confidence: 84%
“…We previously reported that the transport properties of FETs based on κ‐Br or κ‐Cl are strongly influenced by cooling‐induced 2D strain that is caused by mismatch of thermal expansion coefficients between organic channel and the substrate . The κ‐Br device on SiO 2 /Si substrate exhibited insulating nature, reminiscent of bulk κ‐Cl, suggesting a negative pressure effect of about −50 MPa (Figure e).…”
mentioning
confidence: 92%
See 1 more Smart Citation